Faktor-Faktor Yang Mempengaruhi Pemanfaatan Cyber Extension Oleh Penyuluh Pertanian Di Kota Manado - Sabathini Elizabeth Tamba; Elsje Puline Manginsela; Mex Frans Lodwyk Sondakh (Sam Ratulangi University, 2022)
This study aims to analyze factors that influence the use of Cyber Extension by agricultural extension workers in Manado City. The type of data in this study is primary data obtained directly from interviews and through questionnaires distributed to respondents, namely agricultural extension workers in Manado City. The number of samples in this study amounted to 30 people with data collection techniques using purposive sampling technique. The results of this study indicate that the factors that influence the use of Cyber Extension by agricultural extension workers in Manado City are age, education, training, and media ownership.